Human periodontitis-associated salivary microbiome affects the immune response of diabetic mice. Issue 1 (31st December 2022) - He, Jinzhi; Shen, Xin; Fu, Di; Yang, Yutao; Xiong, Kaixin; Zhao, Lei; Xie, Huixu; Pelekos, Georege; Li, Yan
ABSTRACT: Background: The bidirectional association between periodontitis and diabetes mellitus has been well accepted; however, pathways connecting them remain unclear. Some oral bacteria are able to induce immunologic changes favoring insulin resistance individually. However, it is unclear if and how the systemic immune system responds to a disturbed oral microbial community in diabetic sufferers. Aim: This study aimed to investigate the impact of the human periodontitis-associated salivary microbiome on the splenic immune responses of diabetic mice. Methods: An in vivo diabetic animal model was established by feeding high fat food. After microbial depletion with quadruple antibiotic treatment, human saliva from healthy and periodontitis volunteers was transplanted into the mouth of these diabetic mice (N = 3), respectively. Results: Osteoclasts and expression levels of TNF-α and IL-1β were significantly increased in periodontal tissues of mice receiving periodontitis patients donated microbiome compared to these transplanted with healthy subjects donated microbiome. The proportion of monocyte (an innate immunocyte) decreased in mice receiving periodontitis patients donated microbiome. However, the abundance of an adaptive immunocyte Th17 was up-regulated. The IL17 production of ILC3 cells in human periodontitis-associated salivary microbiome recipient mice was significantly impaired. Conclusions: A disturbed oral microbiome imposes a stress on the splenic immune responses of diabetic mice.